Inovasi Pengolahan Labu Kuning Menjadi Selai Di Desa Sekip - Yeni Rafita Sihombing; Melkyory Andronicus; Annisa Nauli Sinaga (Universitas Pahlawan Tuanku Tambusai, 2022)
Yellow pumpkin is known by the public as just a pumpkin that is used only for processed cooking ingredients as vegetable ingredients lodeh or as kolak. While processed fruit meat is still very less to be used by the people. The purpose of this activity is to train people related to the innovation of processing yellow pumpkin into jam in Sekip Village. Processed pumpkin into jam can have a higher functional value. Making jam from pumpkin is one of the efforts to help housewives to have skills that can help their family finance in pandemic conditions. The methods of this activity is socialization in the form of lectures, discussions, questions and answers and train people to make jam. The results of this activity are the housewives can make jam from yellow pumkin and the formation of micro-businesses among the housewives.